2020
DOI: 10.1108/er-03-2020-0124
|View full text |Cite
|
Sign up to set email alerts
|

Innovative work behavior in SMEs: the role of transformational leadership

Abstract: PurposeThe purpose of this paper is to investigate the determinants of innovative work behavior (IWB) by examining the moderating role of transformational leadership in the context of small and medium enterprises (SMEs).Design/methodology/approachThe study surveyed 371 employees from SMEs in Bosnia and Herzegovina by adopting convenience sampling. Hierarchical regression was used to test the hypotheses.FindingsThe findings supported the authors’ assumptions that IWB determinants such as psychological empowerme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 67 publications
0
43
0
4
Order By: Relevance
“…Innovative behavior, as a single construct, is defined as the behavioral patterns of an employee focused on the development and implantation of novel ideas, adoption of new technologies, and environmental processes to achieve the firm's desired objectives and improve performance to attain substantial growth in competitive markets (Chang et al, 2021). Knezović and Drkić (2020) proposed that employees' innovative behavior may help in increasing the efficacy of SMEs by initiating newness, adoption, and modified firm-based resources. Employees' innovative behavior is significant and essential for SMEs to increase their survival (Blanchard, 2017).…”
Section: Employee Innovative Behaviormentioning
confidence: 99%
“…Innovative behavior, as a single construct, is defined as the behavioral patterns of an employee focused on the development and implantation of novel ideas, adoption of new technologies, and environmental processes to achieve the firm's desired objectives and improve performance to attain substantial growth in competitive markets (Chang et al, 2021). Knezović and Drkić (2020) proposed that employees' innovative behavior may help in increasing the efficacy of SMEs by initiating newness, adoption, and modified firm-based resources. Employees' innovative behavior is significant and essential for SMEs to increase their survival (Blanchard, 2017).…”
Section: Employee Innovative Behaviormentioning
confidence: 99%
“…Though studies have identified few mediating factors such as organizational support and empowerment (Jung, Chow, & Wu, 2003), follower’s creativity (Gumusluoğlu & Ilsev, 2009), social capital (Cortes & Herrmann, 2019) and organizational learning and culture (Fernandes, Vasconcelos, & Dobelin, 2018; Sethibe, 2018; Tipu, Ryan, & Fantazy, 2012), the literature is still theoretically undeveloped in terms of specifying employee behaviors that facilitate TL to shape innovation. Despite the findings that organizational leadership shapes employee pro-innovative behaviors (Knezović & Drkić, 2020), which, in turn, facilitate innovation outcomes in SMEs (McDowell, Peake, Coder, & Harris, 2018), there is little knowledge available as to how these variables interact in SMEs of developing countries to influence organization innovation. Scholars, therefore, call for further investigations to unveil promising behavioral mechanisms underlying TL’s effect on innovation outcomes (Cortes & Herrmann, 2019; Fernandes, Vasconcelos, & Dobelin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Exploring social exchange processes in Eastern cultures which is collectivist, improves our knowledge of the underlying mechanism behind employee attitudes and behaviours in the globalized business environment. Second, prior research about innovative behaviour reveals that the majority of these studies were conducted from the managerial perspective, overlooking the employees' side (Knezovi c and Drki c, 2020). We focused the present study from the employees' perspective, as the employees are the cornerstone behind innovation, and firms are actively hiring and retaining employees with entrepreneurial talent.…”
Section: Introductionmentioning
confidence: 99%